2014
DOI: 10.1016/j.jcrs.2014.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of keratometric astigmatism after limbal relaxing incisions

Abstract: Dr. Borasio is the creator of Astig Plot. No other author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Thus, different incision sites (on-axis, superior, superonasal, superotemporal, and temporal), limbal relaxing incisions (LRI), and toric intraocular lenses (IOL) are astigmatism correction strategies in cataract surgery. To date, the efficiency of these methods has been evaluated in different studies [16,21,23,[25][26][27][28][29][30][31][32][33]. Among astigmatism correction methods, the choice of incision site is the oldest method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, different incision sites (on-axis, superior, superonasal, superotemporal, and temporal), limbal relaxing incisions (LRI), and toric intraocular lenses (IOL) are astigmatism correction strategies in cataract surgery. To date, the efficiency of these methods has been evaluated in different studies [16,21,23,[25][26][27][28][29][30][31][32][33]. Among astigmatism correction methods, the choice of incision site is the oldest method.…”
Section: Introductionmentioning
confidence: 99%
“…Among astigmatism correction methods, the choice of incision site is the oldest method. Although recent research has indicated the usefulness of LRI in reducing astigmatism, the technique is not a part of the cataract surgery procedure and is an extra technique [26,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term stability studies of cornealrelaxing incisions are scarce, but it has been reported that the surgically induced astigmatism changes most in the first 10 weeks after surgery, with little change from 10 weeks up to 3 years after surgery. 9 Toric IOLs show the greatest rotation in the early postoperative period with little rotation after 1 week. 10 We conducted the present systematic review and metaanalysis to evaluate the benefits and potential harms of toric implantation to correct preexisting corneal astigmatism in patients undergoing phacoemulsification for age-related cataracts.…”
mentioning
confidence: 99%
“…The largest amount of refractive regression occurs between 1 and 3 months after LRIs, and the refractive status stabilizes between 3 and 6 months postoperatively 21. Another study showed that surgically induced astigmatism continued to change up to 10 weeks after LRIs, but remained stable after 10 weeks and up to 3 years postoperatively 22. We used 6-month follow-up data to exclude the possible effects of refractive regression.…”
Section: Discussionmentioning
confidence: 99%